The Application of TikTok in Instructing Grade 7 Students’ Thai Traditional Dancing Art - Sasina Niyomsuk; Titiworada Polyiem (Journal of Educational Issues, 2024)
The influence of social media on education has been glowing in the last decade, and it shows a potential path to develop learners’ practical skills. The purposes of the study were to investigate the effectiveness of TikTok as a supportive activity on grade 7 students’ Thai traditional dancing art learning achievement and to investigate the students’ satisfaction with the learning activity of TikTok in a Thai traditional dancing art classroom. The participants were 35 grade 7 students in a public school in Thailand. They were selected using a cluster sampling method using their section as the main sampling criteria. The instruments were learning management designed using the model of teaching practical skills with TikTok activities, a Thai traditional dancing art evaluation form, and a satisfaction questionnaire. The data were analyzed using percentage, mean score, standard deviation, single sample t-test, and effectiveness index with the determining criterion of 80. The study’s findings indicate that the integration of Davies’ practical skill instruction approach and TikTok application helped develop the Thai traditional dancing art performances of the participants and it led to a satisfying learning experience for students. Therefore, teaching staff should consider using social media in performing art instruction. Likewise, the result also benefits scholars who seek to understand the impact of social media on practical skill development.